EXTH-38. NEOADJUVANT PD1 BLOCKADE ALTERS THE TUMOR IMMUNE MICROENVIRONMENT AFTER SURGERY IN A PRECLINICAL MODEL OF RECURRENT GLIOBLASTOMA. (14th November 2022) - Hoang-Minh, Lan; Klippel, Kelena; Doonan, Bently; Von Roemeling, Christina; Trivedi, Vrunda; Yang, Changlin; Sriharan, Akshayaa; Francis, Connor; Shin, David; Karachi, Aida; Galochkina, Zhanna; Sarkisian, Matthew
Abstract: SIGNIFICANCE: Promising clinical trials for glioblastoma are evaluating the efficacy of neoadjuvant immunotherapy in the context of recurrent tumor surgery. OBJECTIVE: We investigated the effects of neoadjuvant PD1 blockade on the glioma tumor microenvironment after surgery in a clinically relevant murine model of recurrent tumor. RESULTS: Using a mouse resection model of KR158 glioblastoma that we established, we show that neoadjuvant PD1 inhibition and surgery enhance mouse survival and enhance the recruitment of CD8+ and CD4+ T cells at recurrent tumor sites following bulk tumor resection when compared with surgery followed by adjuvant immunotherapy. Transcriptome and spatial genomic analyses reveal alterations in immune exhaustion and activation pathway signaling genes after neoadjuvant anti-PD1 treatment when compared with adjuvant anti-PD1-treatment or surgery alone. CONCLUSIONS: These studies provide insights into the effects of neoadjuvant PD1 blockade on the tumor microenvironment after surgery and uncover additional treatment targets that could be used in combination with this neoadjuvant therapy.